THE ROLE OF THERMODYNAMICS IN ENERGY-EFFICIENT BUILDING DESIGN FOR SUSTAINABLE ENGINEERING - Jaiswal, Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper explores the critical role of thermodynamics in the design of energy-efficient buildings, emphasizing its significance in promoting sustainability within the built environment. The study examines key components, including thermal insulation, glazing technologies, ventilation strategies, and smart building automation, each contributing to enhanced energy performance and occupant comfort. By applying thermodynamic principles, buildings can significantly reduce energy consumption while maintaining indoor air quality and thermal comfort. The analysis reveals that advanced glazing technologies, such as low-emissivity coatings and multi-pane windows, can decrease energy loss by up to 50%, while effective ventilation strategies can lower energy demand by as much as 60%. Additionally, the integration of smart technologies allows for real-time monitoring and optimization of energy use, achieving savings of 15-30% compared to traditional systems. The findings underscore the need for a holistic approach that combines these elements to achieve significant energy efficiency gains. Ultimately, this research highlights the potential of thermodynamics to facilitate innovative design solutions that contribute to sustainable building practices and reduced environmental impact.